2009
DOI: 10.1080/13557850903248621
|View full text |Cite
|
Sign up to set email alerts
|

HPV knowledge, attitudes, and cultural beliefs among Hispanic men and women living on the Texas–Mexico border

Abstract: Background U.S., Hispanic women have higher cervical cancer incidence rates than non-Hispanic Whites and African Americans and lower rates of cervical cancer screening. Knowledge, attitudes, and cultural beliefs may play a role in higher rates of infection of HPV and decisions about subsequent diagnosis and treatment of cervical cancer. Study aim To explore the level of HPV knowledge, attitudes, and cultural beliefs among Hispanic men and women on the Texas-Mexico border. Methodological Approach Informed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
85
0
10

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(102 citation statements)
references
References 51 publications
(51 reference statements)
7
85
0
10
Order By: Relevance
“…Although this service is offered free of charge, women do not have this test of keep reluctant to do it. In literature (Gupta et al, 2002;Holroyd et al, 2004;Fernandez et al, 2009), traditional values as well as the level of knowledge are reported to be important in the application of such health behaviors as Pap test. In a study on various women of different ethnic groups, such as Indian, Indo-Canadian, Canadian, East Asian and Euro-Canadian Women (Brotto et al, 2008), Pap test behaviors of the Indian and East Asian women groups were found as lower than those of the Euro-Canadian women.…”
Section: Discussionmentioning
confidence: 99%
“…Although this service is offered free of charge, women do not have this test of keep reluctant to do it. In literature (Gupta et al, 2002;Holroyd et al, 2004;Fernandez et al, 2009), traditional values as well as the level of knowledge are reported to be important in the application of such health behaviors as Pap test. In a study on various women of different ethnic groups, such as Indian, Indo-Canadian, Canadian, East Asian and Euro-Canadian Women (Brotto et al, 2008), Pap test behaviors of the Indian and East Asian women groups were found as lower than those of the Euro-Canadian women.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] Low levels of HPV and HPV vaccine awareness and knowledge among Latinos in a variety of U.S. regions have been demonstrated in several studies. [9][10][11] However, a number of studies showed that when the HPV vaccine is presented as a strategy to prevent cervical cancer, support for vaccine uptake is high among Latinas and Latino parents. 10,12,13 Collaborations with community-based partners who can inform the style, content, and relevancy of cancer education messages result in the most effective cancer prevention outreach efforts.…”
mentioning
confidence: 99%
“…The views of machismo, extolling the male virtues of responsibility to family and community, honor, and humility, are another cultural factor identified. Fernandez et al (2009) found positive attributes associated with machismo such as taking responsibility for family health issues and being a knowledgeable caretaker in their study of human papilloma virus (HPV) infection among Hispanic men and women living on the Texas-Mexican border. Their research documented how the Hispanic men's cultural obligation to be healthy can serve to instigate health care-seeking behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Another attribute was cultural views toward death and a fatalistic acceptance of God's will (Fernandez et al, 2009). One participant with ESRD talked about the reactions she received:…”
Section: Cultural Valuesmentioning
confidence: 99%